2017
DOI: 10.1002/1873-3468.12786
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage metabolism in atherosclerosis

Abstract: A key aspect of atherosclerosis is the maladaptive inflammatory response to lipoprotein accumulation in the artery. The failure to decrease lipid accumulation, to clear apoptotic cells, and to resolve inflammation ultimately leads to macrophage accumulation within the vascular wall [Thorp EB (2010) Apoptosis 15, 1124–1136; Moore K et al. (2013) Nat Rev Immunol 13, 709–721; Moore KJ and Tabas I (2011) Cell 145, 341–355; Ley K et al. (2011) Arterioscler Thromb Vasc Biol 31, 1506–1516]. Several subsets of macroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
85
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 184 publications
(254 reference statements)
3
85
0
1
Order By: Relevance
“…Macrophage ingests lipids (such as triglycerides and cholesterol) from lipoprotein and thus transforms into lipid‐rich foam cell . Accelerated transformation of macrophage‐derived foam cell that occurs in the initial stage of atherogenesis is a hallmark of vascular diseases . In the current study, we found that TMS treatment significantly decreased the number of macrophages and macrophage‐derived foam cells in aortic sinuses of ApoE knockout mouse.…”
Section: Discussionsupporting
confidence: 57%
“…Macrophage ingests lipids (such as triglycerides and cholesterol) from lipoprotein and thus transforms into lipid‐rich foam cell . Accelerated transformation of macrophage‐derived foam cell that occurs in the initial stage of atherogenesis is a hallmark of vascular diseases . In the current study, we found that TMS treatment significantly decreased the number of macrophages and macrophage‐derived foam cells in aortic sinuses of ApoE knockout mouse.…”
Section: Discussionsupporting
confidence: 57%
“…[57][58][59] Mox macrophages differ from the other cell types in expressing oxidized 1palmitoyl-2-arachidonoyl-sn-glycero-3-phosphorylcholine and producing HO-1 and sulfiredoxin-1. [60][61][62] Mox macrophages are also associated with triggering of oxidative responses (Table 1). [60][61][62] Arg1.…”
Section: Macrophage Phenotypesmentioning
confidence: 99%
“…[60][61][62] Mox macrophages are also associated with triggering of oxidative responses (Table 1). [60][61][62] Arg1. IRF4, SOCS1, GATA3, CCL4, CCL13, CCL17, CCL18, MRC1, STAB1, MARCO, CD163, FN, TGFB1, MMP1, MMP12, TG, F13A1, TGM2, ADORA3, TGFBR2, IL17RB, ALOX15, The recently discovered M3 macrophages are known as commuting macrophages.…”
Section: Macrophage Phenotypesmentioning
confidence: 99%
“…During atherosclerosis progression, macrophages participate in the local inflammatory responses by secreting cytokines, free radicals, proteases, and various supplements, and mediate low-density lipoprotein (LDL) oxidation by producing reactive oxygen species and reactive nitrogen species, and forming oxidized LDL (ox-LDL) (Bories and Leitinger, 2017;Wong et al, 2017;Xiao et al, 2017). During atherosclerosis progression, macrophages participate in the local inflammatory responses by secreting cytokines, free radicals, proteases, and various supplements, and mediate low-density lipoprotein (LDL) oxidation by producing reactive oxygen species and reactive nitrogen species, and forming oxidized LDL (ox-LDL) (Bories and Leitinger, 2017;Wong et al, 2017;Xiao et al, 2017).…”
Section: Introductionmentioning
confidence: 99%